Définir l’ennemi national. La restauration sécuritaire du président égyptien al-Sisi - Laure Guirguis (Revue des Mondes Musulmans et de la Méditerranée)
This paper will shed light on the ideological and symbolical dimensions of Egyptian current counter-revolution through the analysis of President Al-Sisi religious politics. The Egyptian State is the main agent reproducing minoritization-processes of Christians. Hence, analyzing these processes allows understanding the regimes of veridiction (Foucault) that characterize Egyptian authoritarian situation. Authoritarian and identity logics reinforce each other. They are part of “matrix of war” (Jabri 2006) establishing security as a normative concept. Yet, the “Coptic question” both legitimates and challenges this order. It reveals the aporia of the Egyptian-State: in the name of unity-identity, the nation-state constantly defines itself by referring to a founding split, i.e. Muslim-Christian Unity; in the name of security, it steadily reproduces an enemy within.